Analysis of the number of cases and profile of pregnant women with syphilis in the state of Paraná, Brazil from 2007 to 2017 (Research, Society and Development, 2021)
Objective: To know the prevalence of gestational syphilis in the state of Paraná, Brazil over a 10-year period (2007-2017) and the epidemiological profile of pregnant women. Methods: Cross-sectional and descriptive, quantitative study, in which the data of gestational syphilis in the state of Paraná in a period of 10 years was analyzed. We used the data available at the Department of Informatics of the Unified Health System (DATASUS), from the Sistema de Informação de Agravos e Notificação (SINAN). Later, the data were tabulated in Microsoft Excel® 7.0 software. For the database the 399 municipalities of the state were selected and the variables year of notification, health regional, infection by zone of residence, age group, education, race/color and clinical classification. Results: It was possible to observe an increase in the number of cases in the 22 health regions, totaling 11,450 cases in 10 years. As to the profile of pregnant women, in 18 regions the profile was of women from urban areas, with incomplete elementary schooling, of race/color and white, aged 20 to 39 years, and primary clinical classification. In 2 regions, the profile was urban women, with incomplete primary education, white, aged 20 to 39, and latent clinical classification. In the remaining 2 regions, the profile was urban women, with incomplete elementary school education, of non-white race/color, aged 20 to 39 years, and primary clinical classification. Final considerations: It can be stated that gestational syphilis is a sexually transmitted infection that has been increasing significantly in the state as a whole. It was possible to observe that the profile of most infected pregnant women was urban, with incomplete primary education, white, aged 20 to 39 years and with primary clinical classification.